Writing skills deficiency in English for specific purposes (Esp): English for computer science - Dewi Sari Wahyuni; Darmansyah Darmansyah; Fetri Yeni J (Politeknik Negeri Bali, 2021)
English for Specific Purposes (ESP) taught at Higher Education Institution (HEI) is a kind of course for students majoring other than English. The descriptive research conducted in one of HEI in Pekanbaru, Riau, involved 65 students majoring in Computer Science of that institution. The data gathered by observation and interviews. This research aimed to find out what were the causes of students' weaknesses in English writing skills, for those were the primary problem that they have compared to other English skills. It was revealed those students had 1) low competence in General English (GE) based on CEFR, 2) had a problem with writing, even in their first language, 3) tendency in taking advantage of Google Translate without further checking, 4) lack of knowledge on lexical choice, sentence construction and the structure of writing, 5) limited practicing time and opportunity.